2016
DOI: 10.1111/acel.12493
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cell cohesiveness of outgrowths from eccrine sweat glands delays wound closure in elderly skin

Abstract: SummaryHuman skin heals more slowly in aged vs. young adults, but the mechanism for this delay is unclear. In humans, eccrine sweat glands (ESGs) and hair follicles underlying wounds generate cohesive keratinocyte outgrowths that expand to form the new epidermis. Here, we compared the re‐epithelialization of partial‐thickness wounds created on the forearm of healthy young (< 40 yo) and aged (> 70 yo) adults. Our results confirm that the outgrowth of cells from ESGs is a major feature of repair in young skin. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Reepithelialization already starts some hours after injury by conversion of cobblestone-shaped stationary keratinocytes into flat migratory keratinocytes [22]. In pigs, the epidermis regenerates from hair follicles, apocrine gland ducts, and the wound margin, while in humans, this process seems to originate from pilosebaceous units, eccrine sweat glands [22,23], and the outer root sheath of the hair follicle [24]. Interestingly, the anatomical positioning of skin adnexa seems to be specifically configured for the purpose of highly efficient wound repair.…”
Section: Epithelialization In Skin Wound Healingmentioning
confidence: 99%
“…Reepithelialization already starts some hours after injury by conversion of cobblestone-shaped stationary keratinocytes into flat migratory keratinocytes [22]. In pigs, the epidermis regenerates from hair follicles, apocrine gland ducts, and the wound margin, while in humans, this process seems to originate from pilosebaceous units, eccrine sweat glands [22,23], and the outer root sheath of the hair follicle [24]. Interestingly, the anatomical positioning of skin adnexa seems to be specifically configured for the purpose of highly efficient wound repair.…”
Section: Epithelialization In Skin Wound Healingmentioning
confidence: 99%
“…Whether the injury was too mild to clearly establish that eccrine sweat gland could contribute to epidermal repair in these studies remains a possibility. In humans, complete removal of epidermis triggers a proliferation response that is limited to the absorption portion (straight duct) of the gland (Rittié et al 2016), suggesting that potential sweat gland stem cells are located in the duct and not the coil.…”
Section: Stem Cell Response To Woundingmentioning
confidence: 99%
“…Basal keratinocytes of the advancing tongue (or appendages outgrowths in the case of partial thickness wounds) also harbor characteristics of keratinocyte activation, i.e. mitotic activity [shown in humans: (Williams and Hunter 1957;Rittié et al 2013aRittié et al , 2016], and less desmosomes but more gap junctions than in control epidermis [shown in rats: (Gabbiani et al 1978) and humans: (Ortonne et al 1981)]. It is often cited that keratinocyte migration precedes proliferation during reepithelialization.…”
Section: Leapfrog Mechanism Of Reepithelialization From the Wound Edgementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, care should be taken in selecting a sweat stimulation method, and results from studies involving different methods of sweat stimulation should be compared with caution. It is also worth considering the impact of age on sweat gland cellular functions (66). …”
Section: Introductionmentioning
confidence: 99%